1999
DOI: 10.1093/treephys/19.10.645
|View full text |Cite
|
Sign up to set email alerts
|

Localized graft incompatibility in pear/quince (Pyrus communis/Cydonia oblonga) combinations: multivariate analysis of histological data from 5-month-old grafts

Abstract: To characterize the structural events associated with incompatibility of graft development, we conducted a histological study of compatible and incompatible pear/pear and pear/quince grafts that had been grown for five months in a greenhouse. Multivariate analysis of histological data describing the structure of the graft union allowed us to discriminate between compatible and incompatible combinations before either macroscopic examination or qualitative microscopic examination differences between graft combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
6

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 19 publications
4
28
0
6
Order By: Relevance
“…Está associada a uma má formação estrutural do ponto de união, podendo resultar em ruptura do enxerto (PINA & ERREA, 2009;PEREIRA, 2012), devido à necrose do tecido cambial ou da ausência de diferenciação do tecido vascular na linha de união do enxerto. Plantas com esse tipo de incompatibilidade apresentam desenvolvimento lento, proporcional ao grau de descontinuidade da união (ERMEL et al, 1999;HARTMANN, et al, 2010). Os sintomas externos são pouco evidentes, podendo tardar vários anos para que sejam identifi cados (PINA & ERREA, 2008).…”
Section: Incompatibilidade 'Localizada'unclassified
“…Está associada a uma má formação estrutural do ponto de união, podendo resultar em ruptura do enxerto (PINA & ERREA, 2009;PEREIRA, 2012), devido à necrose do tecido cambial ou da ausência de diferenciação do tecido vascular na linha de união do enxerto. Plantas com esse tipo de incompatibilidade apresentam desenvolvimento lento, proporcional ao grau de descontinuidade da união (ERMEL et al, 1999;HARTMANN, et al, 2010). Os sintomas externos são pouco evidentes, podendo tardar vários anos para que sejam identifi cados (PINA & ERREA, 2008).…”
Section: Incompatibilidade 'Localizada'unclassified
“…Graft unions may lead to incompatibility problems among the grafted parts of plants, there by resulting in more plant death. Many common pear cultivars exhibit graft incompatibility when grafted onto quince (ERMEL et al, 1999). The graft interface exhibits a vascular discontinuity that is associated with the presence of necrotic cells in the wood and bark, the inclusion of unlignified cells in the wood, and invaginations or breaks in the cambium.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cleft grafting favors higher graft survival rate and faster shoot development (BARBOSA et al, 1996;1998). Other studies have reported the production of pear trees grafted onto quince by budding in the winter (ERMEL et al, 1999). On the other hand, in this research, budding accomplished in the summer led to higher sprout length, in spite of the smaller bud sprout percentage.…”
Section: Resultsmentioning
confidence: 49%